Fostering Adaptive Behavior in Students at Risk of Mild Intellectual Disabilities Through the Role of Homeroom Teachers at Public Junior High Schools in Kaubun District (A Case Study at Kaubun Public Junior High School No. 3) - Ahmad Syaifudin; Siti Rohmah Nurhayati (Green Publisher Indonesia, 2026)
The current implementation of adaptive behavior training for students at risk of mild intellectual disabilities at SMP Negeri 3 Kaubun remains suboptimal due to the absence of specialized support teachers. This study was motivated by the importance of adaptive behavior training in enabling students with mild intellectual disabilities to function more independently in their daily lives within the school environment. The study examined how the school fostered adaptive behavior through the role of homeroom teachers in addressing students’ cognitive and social limitations. A qualitative case study approach was employed. Data were collected from three key informants—the parents, the homeroom teacher, and the school principal—through observation, in-depth interviews, and document analysis. Data were analyzed using an interactive qualitative analysis model comprising data collection, data reduction, data display, and conclusion drawing. The findings revealed three main results: students experienced difficulties in processing complex explanations and demonstrated limited social interaction; homeroom teachers implemented seven adaptive strategies, including classroom responsibility agreements, attendance-based rewards, and empathetic communication; and parents reported that their children interacted less socially at home but consistently completed their homework. The study concluded that homeroom teachers played a crucial role in fostering adaptive behavior through structured routines and active school–parent collaboration. However, the lack of inclusive educational infrastructure, limited specialized training, and persistent social stigma remained significant barriers requiring systematic policy intervention.